Multi-stress tolerant PGPR Bacillus xiamenensis PM14 activating sugarcane (Saccharum officinarum L.) red rot disease resistance - Amna; Xia, Ye; Farooq, Muhammad Asad; Javed, Muhammad Tariq; Kamran, Muhammad Aqeel; Mukhtar, Tehmeena; Ali, Javed; Tabassum, Tauseef; Rehman, Shafiq ur; Hussain Munis, Muhammad Farooq; Sultan, Tariq; Chaudhary, Hassan Javed (Plant physiology and biochemistry, 2020)
Sustainability in crop production has emerged as one of the most important concerns of present era's agricultural systems. Plant growth promoting bacteria (PGPB) has been characterized as a set of microorganisms used for enhancing plant growth and a tool for biological control of phytopathogens. However, the inconsistent performance of these bacteria from laboratory/greenhouse to field level has emerged due to prevailing abiotic stresses in fields. Sugarcane crop encounters a combination of biotic and abiotic stresses during its long developmental stages. Nevertheless, the selection of antagonistic PGPB with abiotic stress tolerance would be beneficial for end-user by the successful establishment of product with required effects under field conditions. Stress tolerant Bacillus xiamenensis strain (PM14) isolated from the sugarcane rhizosphere grown in the fields was examined for various PGP activities, enzyme assays, and antibiotic resistance. Strain was screened for in vitro tolerance against drought, salinity, heat stress, and heavy metal toxicity. Inhibition co-efficient of B. xiamenensis PM14 was also calculated against six phyto-pathogenic fungi, including Colletotrichum falcatum (53.81), Fusarium oxysporum (68.24), Fusarium moniliforme (69.70), Rhizoctonia solani (71.62), Macrophomina phaseolina (67.50), and Pythium splendens (77.58). B. xiamenensis is reported here for the first time as the rhizospheric bacterium which possesses resistance against 12 antibiotics and positive results for all in vitro PGP traits except HCN production. Role of 1-aminocyclopropane-1-carboxylate deaminase in the amelioration of biotic and abiotic stress was also supported by the amplification of acds gene. Moreover, in vitro and in vivo experiments revealed B. xiamenensis as the potential antagonistic PGPR and bio-control agent. Results of greenhouse experiment against sugarcane red rot indicated that inoculation of B. xiamenensis to sugarcane plants could suppress the disease symptoms and enhance plant growth. Augmented production of antioxidative enzymes and proline content may lead to the induced systemic resistance against red rot disease of sugarcane. Thus, the future application of native multi-stress tolerant bacteria as bio-control agents in combination with current heat, drought, salinity, and heavy metal tolerance strategy could contribute towards the global food security. •B. xiamenensis PM14, is reported first time for its invitro and invivo antagonistic and PGP activities.•Current strain showed great survival for wide range of environmental variations.•Its inoculation showed suppression of red rot and enhanced sugarcane growth.•First time the inhibition coefficient was also devised against various pathogens.•Antibiotic resistance revealed its potential to survive and compete the native microflora in soil.